The Effectiveness of The Governor's Communication In The Synchronization Of Regional Development In West Java: Study of West Java Governor's KOPDAR Activities - Setiawan, Egy Herdiansyah; Rusli, Budiman; Susanti, Elisa (UNIVERSITAS PAKUAN, 2025)
This research is motivated by the problem of the Provincial Government and Regency/City Government not being in sync in implementing regional development for the community. To overcome this problem, the Governor of West Java created a government communication pattern in the form of Regional Development Communication Activities called “Komunikasi Pembangunan Daerah (KOPDAR)” as an effort to synchronize regional development for the community. The aim of this research is to determine the effectiveness of government communication carried out by the governor during West Java Governor's KOPDAR activities in the context of synchronizing regional development in West Java. In this research, the author used a descriptive method with a quantitative approach. Research data was obtained through distributing questionnaires to 55 respondents who were participants in West Java Governor's KOPDAR activities, interviews, field studies along with observations and literature studies. The research results obtained show that the assessment of the effectiveness of government communication in West Java Governor's KOPDAR activities in the context of synchronizing regional development in West Java is based on indicators of the quality of communicators, information conveyed and media or communication channels in the very high category, while communication indicators and indicators of the communication atmosphere between communicators and communication is in the high category. The conclusion obtained from the results of the research carried out is that the assessment of the effectiveness of the governor's communication in synchronizing regional development in West Java Governor's KOPDAR activities seen from all indicators is in the high category. Thus, government communication carried out during West Java Governor's KOPDAR activities in the context of synchronizing regional development in West Java is said to be effective government communication.